Calcined materials as components of soilless root media: phosphate sorption characteristics and effects on phosphate and water use in greenhouse production of Impatiens wallerana - Ogutu, Rose Atieno (Kansas State University, 2008)
The use of calcined clays contributes properties of nutrient and water retention to soilless root media, which varies greatly depending on the parent clay and calcining treatment. This research characterized phosphate (PO[subscript]4) sorption of various calcined clay products, including low volatile and regular volatile material (LVM and RVM) 2:1 Attasorb clays (Engelhard Corp.), 2:1 Terra Green LVM clays (Oil-Dri Co.), and Turface (Profile Products LLC) at various particle sizes; 1:1 kaolin clays (Thiele Kaolin Co.) in powder form, and diatomaceous earth (Diatomite, Eagle Picher Minerals, Inc.). Three of the calcined materials, Terra Green montmorillonite and Attasorb attapulgite (which had high PO[subscript]4-sorption based on isotherms), and diatomaceous earth (which had negligible PO[subscript]4-sorption) were evaluated as components of soilless root media in two separate greenhouse experiments. The effect of the calcined materials, rate of incorporation (0%, 5%, 10% and 20% by volume in a mix with peat and perlite), and PO[subscript]4-P application rate (0, 5, 15, 45 mg.L[superscript]-1 PO[subscript]4-P) on plant growth, effluent P content and water use were determined during production and post-production of Impatiens wallerana Hook f. 'Tempo Rose'. The calcined materials varied in their ability to adsorb PO[subscript]4-P and generally yielded L-type isotherms. Laboratory results indicated potential for substantive P retention by several of the calcined materials when used in container production. For most materials, PO[subscript]4-P sorption did not show pronounced pH dependence. During production and post-production, the test materials not only improved PO[subscript]4-P retention but also water retention and water use efficiency while still maintaining optimal physical properties at incorporation rates of 5 to 10%. Diatomaceous earth resulted in PO[subscript]4-P retention not significantly different from the calcined clays.
Keywords: Calcined clays; Diatomaceous earth; impatiens wallerana; Soilless media; Peat based; Phosphate retention; Agriculture, Plant Culture (0479); Agriculture, Soil Science (0481)